Distribution of Cigarette Marketing and Cigarette Advertising Around Schools In Badung Regency - Ni Made Kurniati; Ni Putu Widya Astuti; I Nyoman Purnawan (Sean Institute, 2023)
Smoking behavior in adolescents is one of the global problems faced by most countries in the world. The prevalence of smoking among youth aged 10-14 years has increased from 9% in 1995 to 17.4% in 2021. This study aims to determine the distribution of marketing of cigarette products and cigarette advertisements around schools in Badung Regency. Schools were targeted for mapping starting from the elementary, middle and high school/vocational school levels. Cigarette traders and advertisements are carried out by applying a Geographic Information System (GIS). The results showed that most of the observed schools had cigarette sellers around the school. In addition, cigarette advertisements in the form of banners can be found attached to shops or stalls near schools. Cigarette sellers and advertisements are mostly found around Junior High Schools (SMP). The closest distance between cigarette sellers and cigarette advertisements found is 100 meters from the school. The high smoking behavior among young people is related to the density of sales (retail) of cigarettes and the proximity of retail to schools or homes. In addition, cigarette sellers also display attractive tobacco promotions (Tobacco advertisements, promotions and sponsorships/TAPS) at points of sale (Point of Sale/PoS), placed specifically at certain locations and times of purchase. This will increase the chances of smoking initiation among adolescents and hinder smoking cessation efforts for active smokers.